Understanding of elder abuse and neglect among health care professionals in Malaysia: An exploratory survey - Ahmed, A.; Choo, W.Y.; Othman, S.; Hairi, N.N.; Hairi, F.M.; Mohd Mydin, F.H. (Taylor & Francis, 2016)
Elder abuse and neglect (EAN) is a hidden public health challenge for Malaysia. This cross-sectional survey studied the awareness of EAN among 148 doctors and nurses from two neighboring states in Malaysia using a self-administered questionnaire exploring their knowledge, perceptions, practices, and experience concerning EAN. Both doctors and nurses demonstrated poor understanding of signs of EAN and exhibited misperceptions on reporting requirements. Both groups perceived EAN as a national burden and reporting it as their responsibility; but most felt they had not been trained to diagnose it. Many were unsure of procedures and whether their own intervention could be effective. Only four (nurses) of 41 participants who suspected abuse during the past year reported the cases. Targeted education and uniform protocols are mandatory to ensure best practice with regards to EAN. Further research is crucial to extend this inquiry into the broader health care workforce.